Multi-criteria expert based analysis for ranking the urban gentrification drivers in developing countires - Sabri, Soheil; Yaakup, Ahris (2008)

(untitled)
More than 40 years have passed since the term “gentrification” was coined by Ruth Glass (Torrens & Nara, 2007). Originating from Britain, gentrification has become popular concept in developed countries and much research has been conducted in the US, Europe, Canada and Australia since the 1970s on gentrification of the inner cities (Bounds & Mourris, 2008; Hamnett, 1991). Research was also conducted in some premier cities of developing world such as Mexico, Istanbul, Ankara and Seoul (Ha, 2004; Ergun, 2004; Guzey, 2006; Jones & Varley, 1999). Most of the gentrification researchers come to the point that appearance of the already formulated origins of gentrification are time and place-specific (Guzey, 2006), as this urban phenomenon through an evolutionary process found different aspects and drivers. The reason is that through its evolution from late 1950s different preconditions have brought different logics and outcomes in different geographies. Thus it is worth to threat gentrification as a complex phenomenon by sophisticated tools to examine the ideas and hypotheses behind it. In this research it is intended to use the analytical network process (ANP) integrated with GIS to figure out the gentrification drivers in Kuala Lumpur inner city and rank them according to their influence. This would provide a decision support system as tool par excellence for exploring the expert idea based on time and place. Besides, the methodology will foster the future works on modeling and simulating the behaviors of gentrification in developing countries that have not been applied hitherto.